ROLE OF BEHAVIOUR IN MARINE ORGANISMS: POTENTIAL EFFECTS UNDER FUTURE OCEAN CONDITIONS. - SPATAFORA, Davide (Università degli Studi di Palermo, 2021)
Over the last 250 years, the intensive burning of fossil fuels along with industrial processes and land uses (e.g. clearing forests and agriculture) has contributed to an increase in atmospheric CO2 from approximately 280 to 410 ppm, with a further increase (from 730 to 1020 ppm) projected by the end of this century. About 30% of the anthropogenic CO2 has been absorbed by the ocean, with a consequent decrease of the ocean’s surface pH causing a phenomenon better known as Ocean Acidification (OA). The average pH of the surface ocean has declined from 8.2 by 0.1 units since pre-industrial times as a result of CO2 emissions and a further reduction of 0.3–0.5 pH units is expected to occur by the 2100. This increased concentration of atmospheric CO2 has driven an increase in atmospheric and oceanic temperatures enhanced at a rate of ~ 0.2 ̊C per decade in the past 30 years. These rapid changing ocean conditions in pCO2 and temperature are considered two of the major threats to marine biodiversity, leading to changes in the distribution, physiology and behaviour of marine organisms, with potential consequences in community and ecosystem functioning and structure. Despite the increasing interest and amount of literature on this topic, the effects of OA and ocean warming (OW) on marine fauna is difficult to predict, especially because a wide range of impacts have been found across different life stages-and species suggesting that tolerance thresholds to such stressors can vary among life stages experienced by an organism or even between species. In this regard, an increased number of studies has been conducted to better understand the mechanisms by which species can cope with these rapid environmental changes. The first response of animals to a changing environment is predominantly through modification of their behaviour. To date, only a few climate change biology studies have considered behavioural plasticity as a way that animals can adjust their performance under rapid climate change, especially for marine ...